Preservation of Cultural Heritage Buildings with the Adaptive Re-Use Method: A Content Analysis of Past Research - Tri Astuti Ratna Ningsih; Putu Ayu P Agustiananda; Arif Budi Sholihah (Departement of Architecture, Universitas Islam Indonesia, 2022)
Buildings that make adaptive reuse, in general, are buildings that were previously buildings that emphasized their historical values, then changed and disadvantaged changes. In this study, the adaptive reuse building used is a change of function into a building that has value. The purpose of this study is to provide insight and dissect research that discusses adaptive reuse buildings on several continents in the world. Evaluation techniques are carried out by analyzing using tables and grouping each case study from previous research. The methods used in the study are comparative qualitative methods and data analysis using literature studies related to adaptive reuse theory relating to tourism and economic theory. The results of the study, it is expected to provide input and suggestions, which can later be used and used as proof that buildings that have experienced adaptive reuse also have valuable benefits for the building itself and the surrounding environment. Keywords: adaptive re-use; case study; environment; historical value; the continent in the world